Consistency of Condom Use During Receptive Anal Intercourse Among Women and Men Who Have Sex With Men. Issue 7 (July 2015) - D'Anna, Laura Hoyt; Warner, Lee; Margolis, Andrew D.; Korosteleva, Olga A.; O'Donnell, Lydia; Rietmeijer, Cornelis A.; Klausner, Jeffrey D.; Malotte, C. Kevin
<x xml:space="preserve">Abstract</x> Background Unprotected receptive anal intercourse poses HIV risk for men who have sex with men (MSM) and heterosexual women. Little is known about differences in consistent condom use during anal intercourse among these populations. Methods Data were analyzed from a nested study conducted from 2004 to 2005 within a behavioral intervention trial of approximately 40, 000 urban US sexually transmitted disease clinic patients. Analyses were restricted to women and MSM who reported receptive anal intercourse with at least 1 partner in the prior 3 months at baseline, or 3-month follow-up surveys. Condom use was categorized as consistent (100% of receptive acts) or inconsistent/nonuse (0–99% of receptive acts). Multivariable regression with general estimating equations was used to identify factors associated with consistent condom use within each population. Results Approximately 31% of women and 70% of MSM reported receptive anal intercourse at least once in the past 3 months. Men who have sex with men were significantly more likely to report consistent condom use compared with women. For women, intention to use condoms, partner support for condom use, the belief they could stop having sex when condoms were unavailable, and believing their partner had not given them a sexually transmitted infection (STI) were associated with using condoms consistently. For MSM, intention to use condoms, condom use self-efficacy, perceived partner support for condom use, having a nonmain partner, believing their partner had not given them an STI, and fewer sex acts were associated with consistent condom use. Conclusions Findings confirm the importance of considering anal intercourse when assessing STI/HIV risk in MSM and heterosexual women.